2020
DOI: 10.1177/0098628320964787
|View full text |Cite
|
Sign up to set email alerts
|

First-Generation College Students’ Academic Challenges Understood Through the Lens of Expectancy Value Theory in an Introductory Psychology Course

Abstract: Background: First-generation (FG) college students have been a popular subpopulation to study within educational literature as these students experience many unique challenges in their academic careers causing them to drop out within their first year. This gives courses with high first-time freshman numbers such as introductory psychology courses a unique opportunity to reach many of these students. Objective: The purpose of this study is to examine new perspectives of FG students that may further explain hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
2
11
2
Order By: Relevance
“…Further, what is also of interest is that there were no significant differences via generation status in task values. Previous research has found that FGCS have higher cost value than non-FGCS (Goldman et al, 2020) but that was not corroborated in the current study. Given that the participants in this study were from a fall section of general psychology courses, of which have a high population of first semester students, a possibility is that the cost and stressors of higher education have yet to develop.…”
Section: Fgcs and Non-fgcscontrasting
confidence: 99%
“…Further, what is also of interest is that there were no significant differences via generation status in task values. Previous research has found that FGCS have higher cost value than non-FGCS (Goldman et al, 2020) but that was not corroborated in the current study. Given that the participants in this study were from a fall section of general psychology courses, of which have a high population of first semester students, a possibility is that the cost and stressors of higher education have yet to develop.…”
Section: Fgcs and Non-fgcscontrasting
confidence: 99%
“…To that effect, the purpose of this direct focus on FG and NFG populations is to explore if there are aspects of higher education entry factors that appear to be more influential in predicting performance trends for students in these two broad groups. The benefit of this focus is the potential to identify domains of influence in postsecondary success that are unique for FG learners, leading to potential intervention developments to meet needs for FG learners (see Goldman et al, 2020;Harackiewicz et al, 2014).…”
Section: Generational Status and Higher Education Successmentioning
confidence: 99%
“…Our study extends the literature in a critical way in that we examined motivation, engagement, and achievement across generation status at the domain-general level. Prior studies guided by the SEVT primarily examined these constructs in specific academic domains when accounting for generations status (e.g., Part et al, 2020;Goldman et al, 2021Goldman et al, , 2022. While this work provides useful information about domain-specific motivation, engagement, and achievement between generation status, less is known about college students' expectancy, task value, and engagement for school in general and their impact on school outcomes, taking into account generation status.…”
Section: Introductionmentioning
confidence: 99%